Movimento de expansão da escolarização primária pelo estado de São Paulo (1917-1945) - Oriani, Angélica Pall (UNICAMP - Faculdade de Educação, 2018)
Abstract This paper aims to analyze the expansion of primary school education in the state of São Paulo in the first decades of the twentieth century, confronting information about the population growth and the number of school groups and of isolated schools. Through the organization and the analysis of data, it was possible to confirm that the expansion movement of school education in São Paulo has directed to the West of the state, following the coffee production and the construction of railroads. It is also possible to note the significant presence of school groups in different regions of the territory and the crucial support of isolated schools in spreading education and reaching children in places further away from urban centers.

Resumo O objetivo deste artigo é analisar a expansão da escolarização primária pelo estado de São Paulo nas primeiras décadas do século XX, cotejando informações que se referem ao crescimento demográfico e à quantidade de grupos escolares e de escolas isoladas. Mediante a sistematização e a análise dos dados, foi possível confirmar que o movimento da expansão da escolarização em São Paulo direcionou-se para o oeste do estado, acompanhando a produção cafeeira e a construção das ferrovias. Constatou-se, também, a presença significativa dos grupos escolares nas diversas regiões do território e o apoio decisivo das escolas isoladas na disseminação da educação e no alcance de crianças em locais mais afastados dos centros urbanos.
Expansion movement of primary school education in the state of São Paulo (1917-1945)
Keywords: isolated schools; primary school; school groups; history of education; escola isolada; escola primária; grupo escolar; história da educação